THE CONCEPTION AND SOCIAL APPLICATION TO THE ROSPERITY LEVEL OF TRANSMIGRANT FAMILIES IN TERAMANG JAYA DISTRICT, MUKOMUKO REGENCY - Juliani, Juliani; Erita, Yeni; Keslan, Widya Prari (Pendidikan Geografi, 2013)
This research is aimed at knowing the conception and social application to the prosperity level of transmigrant families in Teramang Jaya District, Mukomuko Regency. The method of research is a qualitative experiment. It is oral and written words from investigated persons.            The subjects of research are communities in Teramang Jaya District consisting of six villages, they are Pasar Bantal Village, Nenggalo Village, Teramang Jaya Village, Bunga Tanjung Village, Pernyah Village and Pondok Baru Village. They are based on the snowball sampling in which the interviews are stopped at the 35th respondent. The technique of data sampling in this research is through field observations and interviews.            On the basis of findings and discussion, it can be obtained as the followings: The prosperity level of transmigrant families in Teramang Jaya District has been well-lived in each village. However, there is a little difference in Pasar Bantal and Nenggalo Village in their own conditions of housing and education; the food and wellbeing they have are similar in  conception and application to Teramang Jaya, Bunga Tanjung, Pernyah and Pondok Baru that have been also well-lived. The lacks of prosperity experienced in Pasar Bantal and Nenggalo are due to incomplete housing layouts and educations because the economic situations in Pasar Bantal and Nenggalo are rather lower than in Teramang Jaya, Bunga Tanjung, Pernyah and Pondok Baru. All these are because of the hard economic situation among the four villages as a result of tight competition in household expenses.